80.7k views
2 votes
5m + 9n If m =-7 and n = 4 Evaluate each expression given the variable replacement

User Defoo
by
7.2k points

2 Answers

2 votes
To solve this expression, we can substitute -7 and 4 in for our variables. This would look like:

5(-7) + 9(4) = -35 + 36

= 1

Therefore, the evaluation process would result in 1 as our answer.
User Andrew Drozdov
by
7.8k points
2 votes

Step-by-step explanation

We are given an expression


5m+9n

We are told to evaluate the expression when m=-7 and n=4

To do so, we will simply substitute m=-7 and n=4 into the question, so we will have


5(-7)+9(4)=-35+36=1

Therefore, the answer is 1

User Simoes
by
7.8k points